The Cambridge encyclopedia of the Jesuits - Worcester, Thomas; Armstrong, Megan C. (Cambridge University Press, 2017)
"Founded in 1540 by Ignatius of Loyola, the Society of Jesus (Jesuits) has been praised as a saintly god-send and condemned as the work of Satan. With some 600 entries written by 110 authors - those inside and outside the order - this encyclopedia opens up the complexities of Jesuit history and explores the current life and work of this Catholic religious order and its global vocation. Approximately 230 entries are biographies, focusing on key people in Jesuit history, while the majority of the entries focus on Jesuit ideals, concepts, terminology, places, institutions, and events. With some 70 illustrations highlighting the centrality of visual images in Jesuit life, this encyclopedia is a comprehensive volume providing accessible and authoritative coverage of the Jesuits' life and work across the continents during the last five centuries"--